Effects of acetylsalicylic acid and acetic acid solutions in VX2 carcinoma cells. In vitro analysis - Saad-Hossne, Rogério [UNESP]; Prado, René Gamberini [UNESP]; Hossne, William Saad [UNESP] (FapUNIFESP (SciELO), 2006)
Purpose: To analyze, in vitro, the effects of acetylsalicylic acid (aspirin) and acetic acid solutions on VX2 carcinoma cells in suspension and to examine the correlation between these effects and neoplastic cell death. Methods: The VX2 tumor cells (107 cells/ml) were incubated in solutions containing differing concentrations (2.5% and 5%) of either acetylsalicylic acid or acetic acid, or in saline solution (controls). Every five minutes, cell viability was tested (using the trypan blue test) and analyzed under light microscopy. Results: Tumor cell viability (in %) decreased progressively and, by 30 minutes, neoplastic cell death had occurred in all solutions. Conclusion: Based on this experimental model and the methodology employed, we conclude that these solutions cause neoplastic cell death in vitro.
Keywords: Acetic acid; Aspirin; Carcinoma; In vitro; acetic acid; acetylsalicylic acid; bicarbonate; sodium chloride; trypan blue; animal cell; carcinoma cell; cell death; cell suspension; cell viability; controlled study; correlation analysis; drug blood level; in vitro study; incubation time; microscopy; nonhuman; Acetic Acid; Animals; Cell Death; Cell Survival; Drug Combinations; Drug Screening Assays, Antitumor; Indicators and Reagents; Microscopy, Fluorescence; Neoplasms, Experimental; Rabbits